The complete chloroplast genome of Bupleurum longicaule var. strictum, an annual herb endemic to China - Lucun Yang; Feng Xiong; Yuanming Xiao; Jingjing Li; Chen Chen; Guoying Zhou (Mitochondrial DNA. Part B. Resources, 2020)
Bupleurum species are well-known for their antipyretic, analgesic, gallbladder and other functions so that they are very popular in traditional Chinese medicine. However, to our knowledge, there is no completed chloroplast genome of Bupleurum genus in China. In the present study, we determined the complete chloroplast genome sequences for Bupleurum longicaule var. strictum using IIumina sequencing. Bupleurum longicaule var. strictum is 155,578 bp which is composed of two inverted repeats (IR: 26,257bp), a large single copy region (LSC: 86,977 bp), and a small single-copy region (SSC: 16,087 bp). The overall AT content is 65.32%. The chloroplast genome includes a total of 51 functional genes including 15 protein-coding genes and 36 tRNA. A total of 10 genes were duplicated in the IR regions including seven tRNA and three protein-coding genes. Phylogenetic analysis suggested that B. longicaule var. strictum formed a monophyletic clade.